Pembuatan Thermostat sebagai Alat Pengatur Suhu di Ruangan Penyimpanan Arsip (Studi Kasus: Pada Kantor Komnas Ham Republik Indonesia Perwakilan Sumatera Barat) - Deri Musrinaldi; Desryeni Desriyeni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2019)
AbstractArchives are records of activities or sources of information recorded in various forms made by institutions, organizations or individuals in the context of carrying out activities. In order for the archives to be intact, a thermostat device is needed. A thermostat is a device that can disconnect and connect an electric current when changing the temperature in an environment that matches the specified temperature setting. To install the thermostat device into the archive storage room, it takes 6 (six) frame making thermostats, namely: a) Air Conditioning, (b) Plugs, (c) Incandescent Lamps, (d) Switches, (e) Thermometers and (f ) Digital Thermsostat. work by itself. Thermostats are very suitable for use in archives that cannot be stable. With a regulated temperature of 27 ° C, the condition of the archives is still very good and does not depend on favors or the presence of ticks in the allocation of books.Keywords: Thermostat, Archive, Temperature Gauge